Complication of Peripheral IV Catheterization in Neonates: A Systematic Review - Yuningsih, Risna; Rustina, Yeni (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Peripheral intravenous catheterization in neonates often results in complications associated with their condition as vulnerable population. Common complications of IV catheterization include infiltration, extravasation, phlebitis, leakage, or even vascular infection which may lead to death among neonates. Complications of peripheral IV catheterization are still being investigated in studies in order to identify the incidence and risk factors.Objective: This systematic review aimed to identify complications of peripheral intravenous catheterization in neonates and its risk factorsMethods: Literature searching involved databases such as Science Direct, Scopus, EBSCOhost and SAGE Journals for articles published between 2009-2018 with key words of peripheral intravenous; complication; phlebitis; neonates; risk factor; and infusion therapy. Results: 7 articles addressing peripheral IV catheterization in neonates were included in analysis, revealing three most frequent complications include infiltration, extravasation, and phlebitis. Various factors may affect it. Conclusion: Complication incidence (more than 60%) suggested that the phenomenon is an issue that should be immediately addressed since neonates are part of vulnerable population. It is imperative to continue investigating further in order to identify the incidence and factors affecting it